2019
DOI: 10.1007/s11115-019-00444-6
|View full text |Cite
|
Sign up to set email alerts
|

Public Trust in Local Government: Explaining the Role of Good Governance Practices

Abstract: The primary purpose of this study was to examine the role of good governance practices on public trust in local government. In this study, a conceptual model was developed and tested empirically in Ethiopia by selecting Bahir Dar City Administration. The data analyses yielded the following results. All independent variables were highly influential in describing the public's level of trust in their local government. In this case, participants who perceived the existence of transparency, accountability, and resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
103
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(176 citation statements)
references
References 27 publications
5
103
1
4
Order By: Relevance
“…As stated earlier, trust in government is a result of good governance and may be built up with sound policies (Yousaf et al, 2016;Popovski, 2010;Salminen & Ikola-Norrbacka, 2010 as cited in Beshi & Kaur, 2020). On the other hand, Christensen and Laegreid (2005) link improved performance in public services to trust in government and distrust to poor performance.…”
Section: Governance and Trust In Governmentmentioning
confidence: 98%
“…As stated earlier, trust in government is a result of good governance and may be built up with sound policies (Yousaf et al, 2016;Popovski, 2010;Salminen & Ikola-Norrbacka, 2010 as cited in Beshi & Kaur, 2020). On the other hand, Christensen and Laegreid (2005) link improved performance in public services to trust in government and distrust to poor performance.…”
Section: Governance and Trust In Governmentmentioning
confidence: 98%
“…The concept of "governance" [21] is notoriously complex and is applied to the decision-making processes. It is a multi-level and broad concept which works on all social levels, such as households, villages, towns, nations, regions, or the world [22].…”
Section: What Is Governance?mentioning
confidence: 99%
“…One aspect of GG thus relates to accountability, forcing the state to focus on clear goals, effective policies, and implementing policies of surveillance and reporting mechanisms. In a study by Beshi and Kaur (2019) [22] in Ethiopia, which selected Bahir Dar City, it was estimated that the perceived accountability practices would significantly influence public confidence in local government. The results have shown that the perceived responsibilities affect the public's trust in local government considerably.…”
Section: Good Vs Poor Governancementioning
confidence: 99%
See 2 more Smart Citations